Similar and Different Aspects of the Etymology of English and Uzbek Food Names (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article is devoted to the similarities and differences between the etymology of English and Uzbek food names. Information about the meanings and translations of food names in English and Uzbek languages is also included in this work.